2016
DOI: 10.1186/s12887-016-0718-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of Epstein-Barr virus–associated hemophagocytic lymphohistiocytosis with severe cardiac complications

Abstract: BackgroundHemophagocytic lymphohistiocytosis (HLH) is a life threatening hematological disorder associated with severe systemic inflammation caused by an uncontrolled and ineffective immune response resulting in cytokine storm. Epstein-Barr virus (EBV) is the most common infectious agent in patients with the viral-associated HLH. Limited numbers of cases with cardiac complication have been demonstrated in other viral-associated HLH patients. Herein, we report a pediatric case of severe EBV-associated HLH with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…There is considerable overlap between these conditions in terms of pathophysiology, such as increased serum levels of IL-6, IL-8, TNF-α and soluble IL-2 receptor [ 12 ]. Some studies indicated that EBV-infected CD8 + T cells and high levels of the cytokines in EBV-HLH may play some role in development of coronary artery lesions [ 12 , 13 ]. Recent studies have shown that the serum levels of soluble CD163 and the soluble tumor necrosis factor receptor II/I ratio were significantly elevated in patients with EBV-HLH compared to those in patients with acute-phase KD [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable overlap between these conditions in terms of pathophysiology, such as increased serum levels of IL-6, IL-8, TNF-α and soluble IL-2 receptor [ 12 ]. Some studies indicated that EBV-infected CD8 + T cells and high levels of the cytokines in EBV-HLH may play some role in development of coronary artery lesions [ 12 , 13 ]. Recent studies have shown that the serum levels of soluble CD163 and the soluble tumor necrosis factor receptor II/I ratio were significantly elevated in patients with EBV-HLH compared to those in patients with acute-phase KD [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological complications were not rare, including direct viral damage and secondary immunity damage with diverse and nonspecific manifestations and good prognosis 26 . In addition, EBV infection can cause rare complications of hematological, 27 cardiovascular, 28 and genitourinary 29 systems. EBVRI was prone to multi‐systemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the link between this unusual association, we performed a structured Medline search and found only nine reported cases of cardiac complications associated with HLH 4–12. Most of these cases were reported in children (five in nine) with only three cases reported in adults.…”
Section: Discussionmentioning
confidence: 99%